Anti-calreticulin antibodies and calreticulin in sera of patients diagnosed with dilated or hypertrophic cardiomyopathy. (16th November 2016) - Sánchez, Daniel; Gregor, Pavel; Čurila, Karol; Hoffmanová, Iva; Hábová, Věra; Tučková, Ludmila; Tlaskalová-Hogenová, Helena
Abstract: Distinct cellular level of the Ca 2+ -binding chaperone calreticulin (CRT) is essential for correct embryonal cardiac development and postnatal function. However, CRT is also a potential autoantigen eliciting formation of antibodies (Ab), whose role is not yet clarified. Immunization with CRT leads to cardiac injury, while overexpression of CRT in cardiomyocytes induces dilated cardiomyopathy (DCM) in animals. Hence, we analysed levels of anti-CRT Ab and calreticulin in the sera of patients with idiopatic DCM and hypertrophic cardiomyopathy (HCM). ELISA and immunoblot using human recombinant CRT and Pepscan with synthetic, overlapping decapeptides of CRT were used to detect anti-CRT Ab. Serum CRT concentration was tested by ELISA. Significantly increased levels of anti-CRT Ab of isotypes IgA ( p < 0.001) and IgG ( p < 0.05) were found in patients with both DCM (12/34 seropositive for IgA, 7/34 for IgG) and HCM (13/38 seropositive for IgA, 11/38 for IgG) against healthy controls (2/79 for IgA, 1/79 for IgG). Titration analysis in seropositive DCM and HCM patients documented anti-CRT Ab detected at 1/1600 dilution for IgG and 1/800 for IgA (and IgA1) and at least at 1/200 dilution for IgA2, IgG1, IgG2 and IgG3. Pepscan identified immunogenic CRT epitopes recognized by IgA and IgG Ab of these patients. Significantly increased levels of CRT relative to healthy controls were found in sera of patients with HCM ( p < 0.01, 5/19). These data extend the knowledge of seroprevalence of anti-CRT Ab and CRT, and suggest possible involvement of autoimmune mechanisms directed to CRT in some forms of cardiomyopathies, which are clinically heterogeneous.